Nutrient Balance and Economic Analyses of P Fertilization on an Acid Upland Soil in Sumatra - DJOKO SANTOSO; I GEDE PUTU WIGENA; R.D.B LEFROY (Jurnal Tanah dan Iklim (Indonesian Soil and Climate Journal), 2001)
Soil and crop responses to P fertilization were assessed for seven seasons, from rainy season 1997/1998 until rainy season 2000/2001, in a field experiment at Pauh Menang village of Jambi province, Indonesia. An incomplete factorial combination of six levels of inorganic P (0, 19, 38, 57, 76 and 95 kg P ha-1 as SP-36), two sources organic matters (FYM and stylo), and lime, was laid out in a randomized complete block design with four replicates. The soil in this site was very P deficient and application of 38 kg P ha-1 increased corn yields significantly from less than 1.0 to about 3.5 t ha-1 for the first four crops. The higher rates of applied P didn’t increase further corn yields, indicating that external P requirement was fulfilled. A build-up and maintenance rate of banded application of SP-36,that required in this soil was 38 and 19 kg P ha-1, respectively. Broadcast application for the entire topsoil layer in a plot or farmland would require considerably larger amount of P fertilizer for building up of P level than the banded application. The balances of P treatments were all positive and substantiated by the increasing Colwell P content of the soil with increasing rate of applied P. Although no apparent symptom of Zn deficiency was observed, the Zn content in plant leaf decreased with increasing rate of applied P. By assuming all labour costs as cash costs in conducting economic analyses to calculate the B/C ratios, in general only the SP-36 treatments gave beneficial returns. Although many of the B/C ratios were less than 1.0, the amount of total benefits that could be earned by farmers were considerably high because the total production costs included all labour costs.